An open chat with…Stuart Ferguson. Issue 10 (21st September 2021) - Wright, Duncan; Ferguson, Stuart J.
Abstract : Stuart Ferguson has been on the Editorial Board of FEBS Open Bio since its inception, and his expertise, dedication, and support have been invaluable for the journal's growth and success. Stuart Ferguson received his doctorate in biochemistry from the University of Oxford, before taking up a faculty position at the University of Birmingham and later returning to Oxford, where he is currently Emeritus Fellow at St Edmund Hall but still teaching and pursuing his research interests. Stuart is also a long‐term member of the Editorial Board of our fellow FEBS Press journal, FEBS Letters . Stuart has kindly volunteered to be the second member of our Editorial Board to be interviewed, in celebration of the journal's upcoming 10th anniversary. Abstract : As FEBS Open Bio approaches its 10th anniversary, we have decided it is an ideal time to give the members of our prestigious Editorial Board an opportunity to discuss their research, publishing, and the activities of FEBS in the virtual pages of the journal. Our second interview is with Professor Stuart Ferguson, who has been on the Editorial Board of FEBS Open Bio since its inception, and whose expertise, dedication, and support have been invaluable for the journal's growth and success.